Endovascular Thrombectomy for Pediatric Acute Ischemic Stroke: A Multi-Institutional Experience of Technical and Clinical Outcomes. Issue 1 (6th August 2020) - Ravindra, Vijay M; Alexander, Matthew; Taussky, Philipp; Bollo, Robert J; Hassan, Ameer E; Scoville, Jonathan P; Griauzde, Julius; Awad, Al-Wala; Jumaa, Mouhammad; Zaidi, Syed; Lee, Jonathan J; Hafeez, Muhammad Ubaid; et al.
Abstract: BACKGROUND: Endovascular thrombectomy is a promising treatment for acute ischemic stroke in children, but outcome and technical data in pediatric patients with large-vessel occlusions are lacking. OBJECTIVE: To assess technical and clinical outcomes of thrombectomy in pediatric patients. METHODS: We undertook a retrospective cohort study of pediatric patients who experienced acute ischemic stroke from April 2017 to April 2019 who had immediate, 30-, and 90-d follow-up. Patients were treated with endovascular thrombectomy at 5 US pediatric tertiary care facilities. We recorded initial and postprocedural modified Thrombolysis in Cerebral Infarction (mTICI) grade ≥ 2b, initial and postprocedural Pediatric National Institutes of Health Stroke Scale (PedNIHSS) score, and pediatric modified Rankin scale (mRS) score 0 to 2 at 90 d. RESULTS: There were 23 thrombectomies in 21 patients (mean age 11.6 ± 4.9 yr, median 11.5, range 2.1-19; 52% female). A total of 19 (83%) thrombectomies resulted in mTICI grade ≥ 2b recanalization. The median PedNIHSS score was 13 on presentation (range 4-33) and 2 (range 0-26) at discharge (mean reduction 11.3 ± 6.1). A total of 14 (66%) patients had a mRS score of 0 to 2 at 30-d follow-up; 18/21 (86%) achieved that by 90 d. The median mRS was 1 (range 0-4) at 30 d and 1 (range 0-5) at 90 d. One patient required a blood transfusion after thrombectomy. CONCLUSION: In this large series of pediatric patients treated with endovascular thrombectomy, successful recanalization was accomplished via a variety of approaches with excellent clinical outcomes; further prospective longitudinal study is needed. Graphical Abstract: